UPHOLDING HUMAN RIGHTS AND DEMOCRACY: THE INTERSECTION OF INTERNATIONAL LAW - Qaisar Farooq; Maseeh Ullah; Waqar Fazal Mahar, (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2023)
This research article delves into the intricate relationship between human rights, democracy, and international law, examining their fundamental principles, challenges, and advancements. Grounded in the Universal Declaration of Human Rights (UDHR) and other international instruments, the article explores the core tenets of human rights and democracy within the context of global governance. It analyzes the legal frameworks, treaty obligations, and jurisprudence of international courts and tribunals aimed at promoting and protecting these essential principles. Moreover, the article highlights the persistent challenges posed by authoritarianism, structural inequalities, and emerging technologies to the realization of human rights and democratic governance. Through case studies and examples, it illustrates the multifaceted nature of these challenges and the imperative of collective action to address them effectively. Ultimately, the article underscores the vital role of international cooperation, dialogue, and advocacy in upholding human rights and democracy as universal values. It advocates for inclusive and participatory approaches to governance, grounded in the principles of transparency, accountability, and respect for human dignity, to foster peace, stability, and prosperity in an increasingly interconnected world.